CAPABILIDADE COLABORATIVA NA CADEIA DE SUPRIMENTOS E SEUS MECANISMOS: MULTICASOS DA AGROINDUSTRIA DE FRUTAS DO ESTADO DO ESPIRITO SANTO. - Vinagre, Danieltom Ozeias Vandermas Barbosa (2022)
In a supply chain, the collaborative relationship used strategically is designed for companies due to the benefits obtained from the relationship. These benefits translate into collaborative advantage, which is a competitive view of interorganizational advantage. Those involved in the collaborative relationship aim to gain from the development of the supply chain towards disruption and achieving common goals. The present study focuses on the collaborative capability, which is contributory for organizations to become able to maintain collaborative relationships in an easy way, and thus obtain collaborative advantage. The components of collaborative capability are: trust; commitment; and communication, which collaborate with each other during a relationship, and for each component there are mechanisms that interact in its functioning. There are still gaps in the literature on the development of collaborative capability, therefore, the present study aimed to investigate how a collaborative capacity, through its components and mechanisms, is developed by the focal company with its suppliers and customers. Secondary data analysis was used as a research strategy, together with the study of multiple cases of primary source, which observed as collaborative relationships of 7 companies in the fruit supply chain. The study provides empirical communication on how companies develop trust, commitment to establish relationships. It was identified that the trust of the collaborative relationship is developed from the competence that the partner has in performing a task, and the acts of benevolence strengthening trust. Commitment is developed through verbal contracts, without the need for government formality, and informal communication is sufficient to meet and facilitate the course of the collaborative relationship. Collaborators look for schemes that collaborative capability plays a translating role in establishing meaningful relationships in the supply chain, and, consequently, how collaborative relationships can generate benefits that turn into collaborative benefits.